Kontribusi Kekuatan Otot Tungkai dan Koordinasi Mata-Kaki Terhadap Akurasi Tendangan ke Gawang - Zainur Zainur; Agus Sulastio (UIR Press, 2019)
This research purposed to determine the contribution of leg muscle strength and eyes-foots coordination toward accurate goal shot of football player club of Belibis FC, Pekanbaru city. This research was experimental design with regression analysis. There were 21 players of Belibis Football Club of Pekanbaru city. There were three kinds of test as instrument in this research such as leg muscle strength test, eye-foot coordination test, toe kick test, and goal shot test. The data was analyzed by using correlation of product moment and the coefficient of determination formula to measure variable’s contribution. Based the research result, it can be concluded that there was contribution of leg muscle strength and eye-foot coordination toward accurate goal shot of Belibis Football Club players amount 21.89%.